Some Mannean glazed bricks from the Little Zab River Basin, Northwestern Iran - Salimi, Salah; Ebrahimipour, Salahaddin; Sorkhabi, Obaid (ARAMAZD: Armenian Journal of Near Eastern Studies, 2019)
The article focusses on geographical area south of the Lake Urmia and on the period of the Iron Age III. This is a time span when settlements such as Rabat I-III, Tepe Paswe and Shinawe become real urban centres dominating the local social environment. Archaeological contexts from excavations of Rabat II reveal the ritual function of the site, which is to be identified as a temple. Among exceptional finds from excavations of this sites are glazed bricks. Examination of these objects deriving both from excavations and illegal diggings in Rabat II and Shinawe survey enables their classification. Particularly from morphological point of view they are classified as half, quarter, square, crenellated, and broken, and in sense of ornamentations as geometric, anthropomorphic, faunal, mythical, and inscriptional. The present data reveal the essential traits of material culture of the region during the period of existence of the Mannean confederation.